Dostop do knjižničnega gradiva na osnovi geografskega položaja - pilotni projekt evropske digitalne knjižnice - Šolar, Renata (Knjižnica, 2007)
In the frames of the European eContentplus project European Digital Library (EDL) a pilot GIS application was integrated in The European Library (TEL) portal. The application was realized in the cooperation between the National and University Library of Slovenia and the Geodetic Institute of Slovenia. The pilot GIS application represents the beginning of the development of digital geolibrary where a map is the starting point leading to different geodifferentiated resources. At the same time, it also represents an upgrade of the static presentation of different kinds of digitised materials in the library, as well as an attempt of interdisciplinary presentation with additional educational value. The goal, content, methodology and the results of the pilot GIS application are presented in the article.
Keywords: digitalne knjižnice; geografski informacijski sistemi; geoknjižnice; digitalna kartografija; digitalizacija; digitization; knjižnično gradivo; kartografsko gradivo